Are primary/elementary school‐based interventions effective in preventing/ameliorating excess weight gain? A systematic review of systematic reviews. (11th March 2020) - Goldthorpe, Joanna; Epton, Tracy; Keyworth, Chris; Calam, Rachel; Armitage, Christopher J.
Summary: This systematic review of systematic reviews addresses a current gap in evidence by synthesizing findings relating to weight management interventions set entirely in primary/elementary schools targeting, diet, and/or physical activity as key strategies. Eight databases were searched for systematic reviews of trials of school‐based interventions targeting children aged 4 to 12 years that looked at biometric and behavioral outcomes. From the 10 selected systematic reviews, we found that interventions designed to promote physical activity or reduce sedentary behavior were most effective for weight loss. Interventions designed to improve diet and nutrition had a small effect on behavioral and cognitive outcomes, and these outcomes could be enhanced through the use of experiential learning. The most effective interventions involved a range of stakeholders in the development process and included parents and families in implementation. This systematic review of systematic reviews offers evidence‐based guidance for the development and implementation of multistrategy weight‐management interventions in primary/elementary schools.